2022
DOI: 10.1002/eap.2565
|View full text |Cite
|
Sign up to set email alerts
|

Plant effects on and response to soil microbes in native and non‐nativePhragmites australis

Abstract: Plant–soil feedbacks (PSFs) mediate plant community dynamics and may plausibly facilitate plant invasions. Microbially mediated PSFs are defined by plant effects on soil microbes and subsequent changes in plant performance (responses), both positive and negative. For microbial interactions to benefit invasive plants disproportionately, native and invasive plants must either (1) have different effects on and responses to soil microbial communities or (2) only respond differently to similar microbial communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In the present study, rst based on the comparison of α-diversity indices including observed species, chao1, Shannon's diversity index and Simpson's diversity index we found that the soil microbial diversity was similar interlineages while slight differences existed intra-lineages. Several previous studies supported our observations as they commonly found a similar soil microbial diversity between the introduced and native lineages especially in freshwater habitats (Bickford et al 2018(Bickford et al , 2020(Bickford et al , 2022Farrer et al 2021). Second, a different generic structure but a similar functional structure was present for the soil bacteria among the four groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, rst based on the comparison of α-diversity indices including observed species, chao1, Shannon's diversity index and Simpson's diversity index we found that the soil microbial diversity was similar interlineages while slight differences existed intra-lineages. Several previous studies supported our observations as they commonly found a similar soil microbial diversity between the introduced and native lineages especially in freshwater habitats (Bickford et al 2018(Bickford et al , 2020(Bickford et al , 2022Farrer et al 2021). Second, a different generic structure but a similar functional structure was present for the soil bacteria among the four groups.…”
Section: Discussionsupporting
confidence: 91%
“…Two speculations were embedded in the effects of plant pathogenic fungi: rst, NAnat is the target of plant pathogenic fungi and plant pathogenic fungi can cause harm to their growth, the bene ts of ectomycorrhizal fungi may be offset by the hurt of plant pathogenic fungi; second, NAnat is not the target of plant pathogenic fungi and plant pathogenic fungi can defend NAnat from the competition from other species (Eppinga et Since the transplanting time is different for the three groups, the fungal structure may differ due to different planting times. From the perspective of interaction between plant traits and soil microbiome, although the soil fungal structure was different among the four groups, the trait discrepancy did not exist for almost all measured traits and the effects of soil fungi on plant traits were likely weak (Bickford et al 2022).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One weakness of this work is that funds were not available to determine the distribution of fungi in these samples. This study now paves the way for future studies to test microbial-plant interactions using controlled greenhouse experiments (Bickford et al, 2022). Elucidating the mechanisms used by invasive plants for a competitive advantage over native species also has broader implications for microbially influenced plant-plant interactions.…”
Section: Phylummentioning
confidence: 87%
“…However, there are few studies on the differences in plant-soil feedback during alpine meadow degradation and recovery based on field experiments. Current research on plant-soil feedback is dominated by controlled field and indoor trials (Bickford et al, 2022;Buchenau et al, 2022;Dan et al, 2022;Dudenhöffer et al, 2022;Huberty et al, 2022), which validate the effects of plant-soil feedback mechanisms on population dynamics and community composition, and these studies have provided insight into the important role of plantsoil feedback mechanisms in community development (Kulmatiski et al, 2006). However, most studies on plant-soil feedback relationships have focused on the individual species level, and fewer study have been conducted at the community level, limiting our understanding of plant-soil feedback during community-based alpine meadow degradation and recovery (De Deyn et al, 2004;Kardol et al, 2006;Kulmatiski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%